2023
DOI: 10.1097/gox.0000000000004942
|View full text |Cite
|
Sign up to set email alerts
|

Facial Anthropometric Norms of the Young Black South African Woman

Abstract: Background: Ethnic pride and the push toward preservation of ethnicity in all areas of aesthetic and reconstructive medicine has created the need for normative facial anthropometric data specific to localized geographical populations. This study aimed to gather a set of soft tissue anthropometric norms for the young Black South African woman and to compare this with international data and neoclassical anthropometric maxims. Methods: In total, 156 Black female students from Sefako Makgatho University between 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…Also, Polk et al reported that preferred profiles were anterior to the E plane in their study. Wilson et al found that in young black South African women, lips showed increased protrusion beyond the Ricketts E-line [8,[12][13][14]. It has been mentioned in literature that protrusive lips are seen in Chinese and Turks when compared to Yemenis and Americans.…”
Section: Lower Lipmentioning
confidence: 99%
“…Also, Polk et al reported that preferred profiles were anterior to the E plane in their study. Wilson et al found that in young black South African women, lips showed increased protrusion beyond the Ricketts E-line [8,[12][13][14]. It has been mentioned in literature that protrusive lips are seen in Chinese and Turks when compared to Yemenis and Americans.…”
Section: Lower Lipmentioning
confidence: 99%